Mine Backfilling in the Permafrost, Part II: Effect of Declining Curing Temperature on the Short-Term Unconfined Compressive Strength of Cemented Paste Backfills - Mamert Mbonimpa; Parrein Kwizera; Tikou Belem (Minerals, 2019)
When cemented paste backfill (CPB) is used to fill underground stopes opened in permafrost, depending on the distance from the permafrost wall, the curing temperature within the CPB matrix decreases progressively over time until equilibrium with the permafrost is reached (after several years). In this study, the influence of declining curing temperature (above freezing temperature) on the evolution of the unconfined compressive strength (UCS) of CPB over 28 days’ curing is investigated. CPB mixtures were prepared with a high early (HE) cement and a blend of 80% slag and 20% General Use cement (S-GU) at 5% and 3% contents and cured at room temperature in a humidity chamber and under decreasing temperatures in a temperature-controlled chamber. Results indicate that UCS is higher for CPB cured at room temperature than under declining temperatures. UCS increases progressively from the stope wall toward the inside of the CPB mass. Under declines in curing temperature, HE cement provides better short-term compressive strength than does S-GU binder. In addition, the gradual decline in temperature does not appear to affect the fact that the higher the binder proportion, the greater the strength development. Therefore, UCS is higher for samples prepared with 5% than 3% HE cement. Findings are discussed in terms of practical applications.